Comparison between Erector Spinae Block and Intercostal Nerve Block in Patients Undergoing Video-Assisted Thoracic Surgery: A Pilot Study - Ribeiro, Matheus; Andrino da Silva, Wallace; Confessor de Sousa, Raphael Klênio; Silva de Morais, André; Porto Câmara, Larissa; Costa de Medeiros Dantas, Jorge Lúcio (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
Introduction: Video-assisted thoracic surgery is a well-known and established technique for the treatment of lung diseases. It is considered less invasive than conventional open thoracotomy and, as a result, provides less pain and less impairment of lung function and the shoulder girdle. Objective: To evaluate the quality of post-anesthetic recovery of patients undergoing video-assisted thoracic lung resection surgery, who received analgesia through erector spinae block or intercostal nerve block, through the application of the Qor-15 questionnaire, 24 hours after anesthesia. Method: This is a pilot project of a randomized clinical trial developed with patients undergoing lung resection surgery at the Hospital Universitário Onofre Lopes (HUOL). In it, 18 patients were randomized into two groups: one (10 patients) received analgesia through intercostal block (INT) and the other (08 patients) underwent erector spinae plane block ESP block). As a primary outcome, we assessed the quality of post-anesthesia recovery between different blocks using the QoR-15 questionnaire, applied 24 hours after the end of anesthesia. As secondary outcomes, the consumption of morphine equivalents in mg/kg in the first 24 hours and the intensity of pain through EVN (0 for absence of pain and 10, worst pain imaginable) at times 1, 3, 6, were recorded. 12 and 24 hours after the end of anesthesia, at rest and after deep inspiration. Results: There was no difference in the anesthetic quality assessed through the application of the QoR-15 questionnaire between the ESP and INT groups. Furthermore, there was no significant discrepancy in the intraoperative dose of fentanyl, numerical visual scale (VNS) at rest and movement and consumption of morphine equivalent in the 24 hours after the surgical procedure. Discussion: The results of our study suggest similar results in relation to analgesia and post-anesthesia recovery in patients undergoing video-assisted thoracic lung resection surgery, showing that the erector spinae block can provide analgesia similar to the intercostal block. The choice of anesthetic method varies according to the anesthetist's personal preference. It should also be emphasized that this is a pilot study and was not designed or developed to provide clinical inference, serving as a guide and foundation for the basis of therapeutic plans and more assertive clinical practices during future research. Conclusion: It's evident the importance of nerve blocks for pain management in video-assisted thoracoscopic surgery (VATS) patients. However, the study's findings must be viewed considering its limitations, which prevents definitive conclusions about the superiority or inferiority of the techniques. There is a necessity for larger, multicenter studies to accurately assess the clinical and statistical significance of these findings.